Optimalisasi Sistem Persediaan Bahan Baku Karet Mentah (Lateks) dengan Metode Lot Sizing (Studi Kasus: PT Abaisiat Raya) - Dina Rahmayanti; Ahmad Fauzan (Jurnal Optimasi Sistem Industri, 2013)
PT Abaisiat Raya is one of the manufacturers of rubber crumb (crumb rubber) in the city of Padang. Latex inventory management system at PT Abaisiat Kingdom basically signinfikan still need improvement. It is based on the planning activities in the warehouse inventory of raw materials firms irregular, thus causing excess stock (over stock) at a time and shortage of stock (stock out) at other times. Process optimization is done with latex inventory system involving factors such as demand forecasting production planning or latex needs during the period of next 12 (in 2012), the costs involved, the waiting time (lead time), the implementation of forecasting methods, determination of size lots (lot sizing), the determination of safety stock (safety stock), and re-ordering time (reorder point), so the output will get a number of requests are for 12 periods ahead, the size of each reservation period, the total cost is required, when re-ordering will be done , as well as how much inventory to latex in the warehouse. Based on these results, it was found that the optimal size of the book is the same as the demand for each period (reservation is made each period) due to a cyclical pattern of demand and decreases throughout the planning period. Value of the stock or safety stock is located in Kg 114,282.20, and re-ordering time (reorder point) to cope with fluctuations do when the stock has reached a level of 333,130.95 kg.Keywords: Forecasting, Time Wait, Lot Size, Safety Supplies, Reorder